Students Apply Research Methods to Consumer Decisions About Cognitive Enhancing Drinks - Walters, Charles B. (J Undergrad Neurosci Educ, 2014)
The goal of this class project was to provide students with a hands-on research experience that allowed autonomy, but eliminated duplication of effort and could be completed within one semester. Our resources were limited to a small supply budget and an introductory psychology subject pool. Six students from a behavioral neuroscience class tested claims made by a drink company that their product improves cognitive function. The students each chose a cognitive task for their part of the project. The tasks included the Donders Reaction Time Task, the Stroop Task, the Raven’s Progressive Matrices, a short-term memory span test, the Rey-Osterrieth Complex Figure Test and a simple measure of prefrontal EEG activity. Participants were randomly assigned to an experimental or control drink. The experimental group received the putative cognitive enhancing drink and the control group received a placebo drink that was very similar in color and taste. The two drinks shared no active ingredients. Results suggest that the putative cognitive enhancing drink did not improve performance on any of the tasks and decreased performance on the short-term memory task. These findings are discussed in regard to implications for consumers as well as further research into supplements and their ability to improve cognitive performance. Each student presented his/her results at a university-wide research conference. This project provided a rich experience in which students had the opportunity to carry out a research project from conception to presentation.